2000
DOI: 10.1034/j.1600-0463.2000.d01-99.x
|View full text |Cite
|
Sign up to set email alerts
|

Changed expression of leukocyte adhesion molecules and increased production of reactive oxygen species caused by Streptococcus pyogenes in human whole blood

Abstract: To elucidate the innate immune responses to group A streptococci (GAS) important in the pathophysiology of sepsis, flow cytometric techniques were applied to study the effects of live and heat-inactivated GAS, including their particulate and soluble components, on the expression of leukocyte adhesion molecules CD11b (Mac-1) and CD62L (L-selectin), and leukocyte production of reactive oxygen species (ROS) in human whole blood. GAS caused marked time- and concentration-dependent increases in CD11b and ROS, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…We analyzed both the percentage of leukocytes expressing the ligand as well as the fluorescence intensity in absolute units; molecular equivalents of soluble fluorochrome (MESF) of the attached antibody as the difference between isotype control and the antibody of interest. The PSGL-1 antibody and isotype control, both FITC-conjugated, were delivered from Ancell Corporation, Bayport, MN, USA and the method for PSGL-1 analysis was adopted from Saetre et al [21] Beads for the standard curve of MESF units were from Bangs Laboratories Inc, Fisher, IN, USA.…”
Section: Study Subjectsmentioning
confidence: 99%
“…We analyzed both the percentage of leukocytes expressing the ligand as well as the fluorescence intensity in absolute units; molecular equivalents of soluble fluorochrome (MESF) of the attached antibody as the difference between isotype control and the antibody of interest. The PSGL-1 antibody and isotype control, both FITC-conjugated, were delivered from Ancell Corporation, Bayport, MN, USA and the method for PSGL-1 analysis was adopted from Saetre et al [21] Beads for the standard curve of MESF units were from Bangs Laboratories Inc, Fisher, IN, USA.…”
Section: Study Subjectsmentioning
confidence: 99%
“…Along with morphological changes, expressions of cell surface molecules such as MHC II and CR3 on the peripheral immune cells were also significantly affected by the gram-positive bacteria and their component, LTA (Carratelli et al, 1996;Saetre et al, 2000;Kolb-Maurer et al, 2000;Jorgensen et al, 2001). This study has demonstrated that just like in the peripheral immune cells, LTA from S. aureus markedly upregulated the surface expression of MHC class II molecules on microglia in vitro.…”
Section: Lipoteichoic Acid Induced An Enhanced Expression Of Mhc Clasmentioning
confidence: 74%
“…These receptors can be modulated by their ligands from the gram-positive bacterial cell walls, such as streptococcal LTA, which significantly increased the expression of complement receptor type 3 on human monocytes (Carratelli et al, 1996) or whole blood leukocytes (Saetre et al, 2000) and CD14 on whole-blood monocytes (Landmann et al, 1996;Saetre et al, 2000;Jorgensen et al, 2001). The modulation of scavenger receptor by LPS has also been evidenced in primary and elicited mouse peritoneal macrophages as well as the J774A.1 and RAW 264.7 mouse macrophage lines (Fitzgerald et al, 2000).…”
Section: Lipoteichoic Acid Induced An Enhanced Expression Of Mhc Clasmentioning
confidence: 99%
“…We showed that keratinocytes are able to produce ROS and this finding is consistent with previous work demonstrating that S. pyogenes is able to induce the production of ROS by HeLa cells and human leukocytes. 29,30 Moreover, transcriptional studies with macrophages infected with GAS demonstrated up-regulation of the p47phox gene encoding a component of the NADPH oxidase (Ncf1), further Figure 5. GAS induces cell death by stimulating O À 2 production.…”
Section: Discussionmentioning
confidence: 92%